TANGGUNG JAWAB PROFESI GURU DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Shelomyta Agustina Sefrina; Luk Luk Amaliya; Ikmawati; Achmad Muhtadin (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study is motivated by the important role of teachers as professional educators in shaping students' character in the midst of increasingly complex societal changes. Teachers are not only responsible for delivering academic content but also act as role models, motivators, and guides in instilling moral values. This study aims to analyze the professional responsibilities of teachers in shaping students’ character. The research employs a qualitative approach using library research by analyzing relevant journals and scientific articles published between 2016 and 2026. The results and discussion indicate that teachers’ pedagogical and professional competencies play a crucial role in the success of character development, as reflected in the internalization of values such as discipline, responsibility, and integrity. Teachers also function as character architects through the stages of moral knowing, moral feeling, and moral action. However, there are challenges arising from external factors, particularly unsupportive family environments. In conclusion, teachers' professional responsibility is a key factor in determining the success of students' character development; therefore, improving teacher competencies and strengthening collaboration between schools and parents are essential to develop students with strong character.